What is the impact of biological treatment on sleep quality in chronic rhinosinusitis with nasal polyps patients: a retrospective cross-sectional study - Danah Althomaly; Mai Almasoud; Arulanantham Zechariah Jebakumar; Khalid Aldilaijan (The Egyptian Journal of Otolaryngology)
Abstract Background Sleep disturbance is prevalent in patients with chronic rhinosinusitis with nasal polyps (CRSwNP). Although biological treatment has been shown to improve overall patient-reported sinonasal symptoms in CRSwNP, the treatment impact on individual sleep quality remains less explored. The purpose of this study is to investigate the effect of dupilumab treatment on sleep quality in patients with CRSwNP. Methods A single-institutional, retrospective chart review was conducted on adult patients who received biological treatment (dupilumab) for CRSwNP. Patients’ condition was assessed before treatment and 3–12 months after continuous treatment. The assessment included the 22-item Sino-Nasal Outcome Test (SNOT-22), Nasal Obstruction Symptom Evaluation (NOSE) scale, Nasal Polyp Score (NPS), as well as perception for anosmia and hyposmia using Visual Analog Scale (VAS) for smell. Sleep-related symptoms and treatment outcomes were assessed using the Pittsburg sleep quality index (PSQI) global score, sleep domain questions within SNOT-22, and sleep-related question in the NOSE scale. Subjects with a PSQI global score of > 5 were considered poor sleepers. Results A total of 15 charts were included in this study. There were 12 males (80%) and 3 females (20%). Sixty percent of them were having bronchial asthma. The mean follow-up duration was around 6.7 months. The patients showed significant improvement in nasal assessment using the median values for SNOT-22, NOSE scale, NPS, and VAS for smell (P-value ≤ 0.001). As well, there was a significant improvement in the median scores for global PSQI, sleep domain questions within SNOT-22, and sleep-related question in the NOSE scale (P-value 0.04, < 0.001, and 0.001, respectively). Eight subjects (53.3%) had poor sleep quality before treatment. Four out of them improved from being poor sleepers to good sleepers after using the treatment. Conclusion This study indicates that dupilumab is an effective treatment for CRSwNP and it improves sleep quality parameters in some patients.